An unexpected occurrence of subsoil krotovinas in southwest Germany - Abel, Cecilia; Herrmann, Ludger; Rethemeyer, Janet; Rennert, Thilo (Discover Soil, 2025)
The accumulation of soil organic matter (SOM) and intensive bioturbation, which may become evident by krotovinas, characterize soils with a mollic/chernic horizon. Krotovinas include SOM-rich fillings in the subsoil, resulting from the burrowing activities of mammals. We studied a soil with subsoil krotovinas by fractionating SOM, 13 C nuclear magnetic resonance (NMR) spectroscopy, and 14 C dating. The soil was located in southwest Germany at 698 m above sea level and 880 mm mean annual precipitation, which is a very unusual location in central Europe for soils with several features typical of a mollic horizon and krotovinas. Despite these morphological features, the soil was classified as Umbrisol. While most of the SOM in the two uppermost Ah horizons was present in aggregates, the majority of the SOM in both the underlying Ah horizon and the krotovina was present in the silt-and-clay fraction. Compared with the other soil horizons, krotovina SOM was most stable against chemical oxidation, showed evidence of black-carbon accumulation, as determined via NMR spectroscopy, and had the highest calibrated 14 C age (3824–3565 years before present). Our results point to soil formation in situ and relictic bioturbation that induced krotovina formation, and they further confirm the importance of black carbon as a contributor to persistent SOM, which is also present in krotovinas. The presence of krotovinas in an Umbrisol and the properties of krotovina-SOM may stimulate further research on similar soils, their distribution and properties, and on classification of these soils.